2010
DOI: 10.1007/s11442-010-0821-6
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation on seasonal transport variations and mechanisms of suspended sediment discharged from the Yellow River to the Bohai Sea

Abstract: Based on sediment and discharge flux data for the Yellow River, realistic forcing fields and bathymetry of the Bohai Sea, a suspended sediment transport module is driven by a wave-current coupled model to research seasonal variations and mechanisms of suspended load transport to the Bohai Sea. It could be concluded that surface sediment concentration indicates a distinct spatial distribution characteristic that varies seasonally in the Bohai Sea. Sediment concentration is rather high near the Yellow River estu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…Most of the sediment deposits locally near the estuary, which was also observed by Zhang et al [10]. Studies [30], [31] have indicated that about 70% of the sediment from Yellow river deposits around the estuary. The river deltas act as a sink for the sediment in summer and as a source for the suspended sediment in winter and for the transport to Yellow sea through Bohai strait.…”
Section: Mechanisms Determining the Spatiotemporal Variation Of R Rssupporting
confidence: 65%
“…Most of the sediment deposits locally near the estuary, which was also observed by Zhang et al [10]. Studies [30], [31] have indicated that about 70% of the sediment from Yellow river deposits around the estuary. The river deltas act as a sink for the sediment in summer and as a source for the suspended sediment in winter and for the transport to Yellow sea through Bohai strait.…”
Section: Mechanisms Determining the Spatiotemporal Variation Of R Rssupporting
confidence: 65%
“…Duo to the influence of East Asian monsoon, the entire water column produces a strong vertical mixing (Bian et al, 2010;Dong et al, 2011;Li et al, 2010;Shi & Wang, 2010;Wang & Jiang, 2008). Previous researchers reported that the temperature decreases significantly with the depth increasing in the period of late fall to early spring.…”
Section: Discussionmentioning
confidence: 99%
“…6. The low salinity plume moves to the headland of Laizhou Bay and has the tendency to turn to the southeast as a result of the influence of the Coriolis force (Li et al 2005a). Particles located at the central of the BS move south, then turn to the southeast and move out from the south of Bohai Strait finally.…”
Section: Surface Circulation Of the Bs During Both The Winter And Thementioning
confidence: 99%